SANITARY-AND-EPIDEMIOLOGIC WELL-BEING OF CHILDREN IN THE RUSSIAN FEDERATION - G. G. Onishchenko; E. B. Ezhlova; A.A. A.A. Melnikova; L. A. Dementyeva; Y. V. Demina; G. V. Yanovskaya; N. A. Fedotova; G. E. Ivanov (Педиатрическая фармакология, 2013)
The article provides a morbidity analysis and covers the epidemiologic process development tendencies in the Russian Federation for a range of infectious diseases, including those controlled by specific preventive measures, and the measures taken to fight them, aimed at preserving Russia’s status as a poliomyelitis-free country, eliminating endemic measles and rubella, reducing hepatitis B and HIV-infection morbidity and preventing influenza and ARVI from spreading on the territory of Russia.The article gives an analysis of how the measures aimed at maintaining sanitary-and-epidemiologic well-being in the process of preschool and school education, including measures of administrative responsibility enhancement for the official and corporate bodies for non-observance of sanitary-and-epidemiologic requirements for the rest and health improvement conditions of children, were fulfilled. An assessment of how aggressive information influences the population's health, especially that of children and adolescents, and measures taken by the Federal service on customers' rights protection and human well-being surveillance to decrease its influence is given. Main goals and activity areas on improving health protection and maintaining sanitary-and-epidemiologic well-being of the citizens.